2019
DOI: 10.1101/770024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission Chains or Independent Solvers? A Comparative Study of Two Collective Problem-Solving Methods

Abstract: AbstractGroups can be very successful problem-solvers. This collective achievement crucially depends on how the group is structured, that is, how information flows between members and how individual contributions are merged. Numerous methods have been proposed, which can be divided into two major categories: those that involve an exchange of information between the group members, and those that do not. Here we compare two instances of such methods for solving complex problems: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Over the years, research on group decision making has employed various paradigms or tasks and it has been shown that, depending on the decision task, different processes might influence group decision performance (Kerr et al, 1996;Moussaïd & Yahosseini, 2016;Yahosseini & Moussaïd, 2019). Steiner (1972) proposed to categorize tasks according to component (i.e., is the task divisible between group members or does it need to be solved together), focus (i.e., does the task require a "good" solution -optimizing, or does it require many different solutions -maximizing), and interdependence (i.e., in which way can group members combine their different contributions to the task).…”
Section: Group Decision Making (Under Uncertainty)mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, research on group decision making has employed various paradigms or tasks and it has been shown that, depending on the decision task, different processes might influence group decision performance (Kerr et al, 1996;Moussaïd & Yahosseini, 2016;Yahosseini & Moussaïd, 2019). Steiner (1972) proposed to categorize tasks according to component (i.e., is the task divisible between group members or does it need to be solved together), focus (i.e., does the task require a "good" solution -optimizing, or does it require many different solutions -maximizing), and interdependence (i.e., in which way can group members combine their different contributions to the task).…”
Section: Group Decision Making (Under Uncertainty)mentioning
confidence: 99%
“…Note that these group distinctions are mainly distinctions of group task design (e.g., within an experiment) and do not necessarily emerge during group interaction. The different task types will affect group decision making in the way they structure a group's environment and either enable or constrain individual contributions (Yahosseini & Moussaïd, 2019). This dissertation will present different task types: In Chapter 3, groups are faced with generally intellective tasks (i.e., tasks that have objectively correct solutions) that require inference of the best option and are low on demonstrability.…”
Section: Group Decision Making (Under Uncertainty)mentioning
confidence: 99%